Allium gilanense, a new species of Allium sect. Codonoprasum (Amaryllidaceae) from Iran: evidence from morphological and molecular data - Bagheri, Ali; Blattner, Frank R.; Fritsch, Reinhard M. (Phytotaxa, 2020)
As a result of recent botanical expeditions to the north of Iran, we describe here a new endemic Allium species from Gilan province named Allium gilanense. Molecular and morphological data indicate that it belongs to Allium sect. Codonoprasum. We provide a morphological description, comparing Allium gilanense with the closest relative taxa A. lenkoranicum and A. paniculatum, the preliminary karyotype of the new species, and molecular phylogenetic data derived from the nuclear ribosomal DNA internal transcribed spacers (ITS) and the chloroplast intergenic spacer trnH-psbA. The chromosome number of the new species is 2n = 16 with 0-3 B chromosomes.